Pengaruh CEO Narcissism Terhadap Kinerja Keuangan Bank (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2022) - Ruth Renatha Siahaan; Suherman Suherman; Titis Fatarina Mahfirah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to determine the effect of CEO Narcissism on the financial performance of banking companies listed on the Indonesia Stock Exchange for the period 2019-2022. The independent variable used in this study is CEO Narcissism which is proxied by the size of the CEO's photo in the company's annual report, the number of social media owned by the CEO, and the size of the CEO's signature. While the dependent variable used in this study is the financial performance of banking companies which is proxied using the Return on Equity (ROE), Return on Asset (ROA), and Net Interest Margin (NIM) ratios. This study also uses control variables in the form of company size, company age and Debt to Asset Ratio (DAR). The number of company samples used in this study were 39 companies with an observation time span of 4 years, resulting in 156 sample observations. The sampling method used is purposive sampling. This study uses panel data regression analysis. The model used in this study is panel data regression with the Random Effect Model (REM) approach. The results of this study indicate that CEO narcissism as measured using the size of the CEO's photo in the annual report, the number of social media owned by the CEO, and the size of the CEO's signature have no significant effect on financial performance as measured using either ROE, ROA, or NIM ratios. This study has limitations, namely the time period in the research sample used is relatively short and the sample used is only banking companies so that further research is expected to extend the research time and increase the sample of companies using samples from other sectors.